A pragmatic parallel arm multi-centre randomised controlled trial to assess the effectiveness and cost-effectiveness of a group-based fatigue management programme (FACETS) for people with multiple sclerosis. Issue 10 (21st May 2013) - Thomas, Sarah; Thomas, Peter W; Kersten, Paula; Jones, Rosemary; Green, Colin; Nock, Alison; Slingsby, Vicky; Smith, Angela Davies; Baker, Roger; Galvin, Kathleen T; Hillier, Charles
Abstract : Background: Fatigue is a common and troubling symptom for people with multiple sclerosis (MS). Aim: To evaluate the effectiveness and cost-effectiveness of a six-session group-based programme for managing MS-fatigue (Fatigue: Applying Cognitive behavioural and Energy effectiveness Techniques to lifeStyle (FACETS)). Methods: Three-centre parallel arm randomised controlled trial with economic evaluation. Patients with MS and significant fatigue were randomised to FACETS plus current local practice (FACETS) or current local practice alone (CLP), using concealed computer-generated randomisation. Participant blinding was not possible. Primary outcomes were fatigue severity (Fatigue Assessment Instrument), self-efficacy (Multiple Sclerosis-Fatigue Self-Efficacy) and disease-specific quality of life (Multiple Sclerosis Impact Scale (MSIS-29)) at 1 and 4 months postintervention (follow-up 1 and 2). Quality adjusted life years (QALYs) were calculated (EuroQoL 5-Dimensions questionnaire and the Short-form 6-Dimensions questionnaire). Results: Between May 2008 and November 2009, 164 patients were randomised; primary outcome data were available for 146 (89%). Statistically significant differences favour the intervention group on fatigue self-efficacy at follow-up 1 (mean difference (MD) 9, 95% CI (4 to 14), standardised effect size (SES) 0.54, p=0.001) and follow-up 2 (MD 6, 95% CI (0 to 12), SES 0.36, p=0.05) and fatigue severity at follow-up 2 (MD −0.36, 95% CI (−0.63 to −0.08), SES −0.35, p=0.01) but no differences for MSIS-29 or QALYs. No adverse events reported. Estimated cost per person for FACETS is £453; findings suggest an incremental cost-effectiveness ratio of £2157 per additional person with a clinically significant improvement in fatigue. Conclusions: FACETS is effective in reducing fatigue severity and increasing fatigue self-efficacy. However, it is difficult to assess the additional cost in terms of cost-effectiveness (ie, cost per QALY) as improvements in fatigue are not reflected in the QALY outcomes, with no significant differences between FACETS and CLP. The strengths of this trial are its pragmatic nature and high external validity. Trial registration: Current Controlled Trials ISRCTN76517470 .